Analysis Of The Effect Of Company Age And Capital Structure On Profitability In Primary Consumer Sector Companies Listed On The Indonesia Stock Exchange - Tjong, William; Hartono, Brigita (Jurnal Penelitian Akuntansi (JPA), 2024)
The purpose of research is to analyze the effect of company age and capital structure on profitability in companies engaged in the primary consumer sector listed on the Indonesia Stock Exchange (IDX). The data used in this study are secondary data that can be accessed through S&P Capital IQ. Furthermore, data processing will be carried out with STATA version 15. Profitability is calculated using Return on Equity (ROE). The age of the company will be measured by how long the company has been listed on the IDX. Capital structure measurement will be done using Debt Equity Ratio (DER). 155 data sets will be used in this study, consisting of 31 companies over a 5-year period. The results of this study, namely (1) company age has a positive and significant effect on profitability and (2) capital structure has a positive and significant effect on profitability.